Bronchodilator responsiveness in children with cystic fibrosis and allergic bronchopulmonary aspergillosis. Issue 2 (27th August 2020) - Pollak, Mordechai; Shaw, Michelle; Wilson, David; Grasemann, Hartmut; Ratjen, Felix
Allergic bronchopulmonary aspergillosis (ABPA) is a hypersensitivity lung disease that occurs in approximately 9% of children with cystic fibrosis (CF) [1]. While ABPA is commonly associated with worsening lung function, differentiating ABPA from other causes of pulmonary function decline often poses a clinical challenge. This is reflected by major differences among the various diagnostic criteria for ABPA that have been suggested to date [2–5]. A positive bronchodilator response (BDR) is characteristic for asthma which is a common co-morbidity in CF patients, but whether this is helpful in differentiating ABPA from other causes of deterioration in lung function is currently unclear. A recent observational study of paediatric CF patients found a significant higher BDR in ABPA compared to patients not sensitised to Aspergillus fumigatus [6]; this stands in contrast to the CF Foundation consensus that did not identify airway obstruction reversibility as a characteristic of CF-related ABPA [5]. We therefore aimed to evaluate the clinical utility of BDR for diagnosis of ABPA in CF by comparing rates of positive BDR prior to a diagnosis of ABPA to CF patients experiencing acute lung function deteriorations for other causes. CF patients with a new diagnosis of ABPA had a similar BD response, compared to CF patients with acute lung function deterioration from other causes. BD response testing did not help differentiating ABPA from other causes of lung function deterioration. https://bit.ly/39Oegnh